Comparison of the Clinicopathologic Characteristics of Intraductal Papillary Neoplasm of the Bile Duct according to Morphological and Anatomical Classifications - Kim, Jae Ri; Lee, Kyoung-Bun; Kwon, Wooil; Kim, Eunjung; Kim, Sun-Whe; Jang, Jin-Young (Journal of Korean medical science, 2018)
Intraductal papillary neoplasm of the bile duct (IPNB) is a recently defined entity and its clinical characteristics and classifications have yet to be established. We aimed to clarify the clinical features of IPNB and determine the optimal morphological classification criteria. From 2003 to 2016, 112 patients with IPNB who underwent surgery were included in the analysis. After pathologic reexamination by a specialized biliary-pancreas pathologist, previously suggested morphological and anatomical classifications were compared using the clinicopathologic characteristics of IPNB. In terms of histologic subtypes, most patients had the intestinal type (n = 53; 48.6%) or pancreatobiliary type (n = 33; 30.3%). The simple "modified anatomical classification" showed that extrahepatic IPNB comprised more of the intestinal type and tended to be removed by bile duct resection or pancreatoduodenectomy. Intrahepatic IPNB had an equally high proportion of intestinal and pancreatobiliary types and tended to be removed by hepatobiliary resection. Morphologic classifications and histologic subtypes had no effect on survival, whereas a positive resection margin (75.9% vs. 25.7%; = 0.004) and lymph node metastasis (75.3% vs. 30.0%; = 0.091) were associated with a poor five-year overall survival rate. In the multivariate analysis, a positive resection margin and perineural invasion were important risk factors for survival. IPNB showed better long-term outcomes after optimal surgical resection. The "modified anatomical classification" is simple and intuitive and can help to select a treatment strategy and establish the proper scope of the operation.